Budaya “Ewuh Pakewuh”, Kecurangan, dan Sistem Whistleblowing: Perspektif Psikologi dan Budaya Berdasarkan Teori Perilaku Terencana - Sampe Tondok, Marselius; Widayati, Irma (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The results of the fraud survey in Indonesia in 2019 show that out of 239 cases of fraud found, 167 cases (69.9%) were related to corruption. Three conditions trigger fraud: pressure, opportunity, and rationalization. Fraud has a harmful impact, whether financial or non-financial, and therefore prevention efforts are needed such as implementating a whistleblowing system. Cultural factors significantly impact the effectiveness of such systems. This study explores the "ewuh pakewuh" culture through the lens of the theory of planned behavior (TPB). When reviewing the three determinants in the TPB, namely attitude toward the behavior, subjective norms, and perceived behavioral control, the "ewuh pakewuh" culture influences the intention of fraud behavior and the whistleblowing system. Literature studies reveal that in cultures with high "ewuh pakewuh" presence, fraud intention is high, and whistleblowing effectiveness is low. Although "ewuh pakewuh" fosters harmony and reduces conflict, courage is needed to report illegal actions for organizational sustainability. Research on "ewuh pakewuh" is more common in government settings, as it is believed to be more prevalent in government institutions than in egalitarian corporate organizations. Further research is necessary to understand this phenomenon and to evaluate how private companies in Indonesia are affected by the "ewuh pakewuh" culture and its impact on their performance.